(untitled) (American International Journal of Sciences and Engineering Research, 2021)
Bangladesh is mainly an agricultural country. Agriculture is the most important occupation for the most of the Bangladeshi families. This study is conducted to develop an automated irrigation mechanism which turns the pumping motor ON and OFF by detecting the moisture content of the earth using the soil moisture sensor without the intervention of human. This Smart irrigation system project is using an Arduino Uno micro-controller, Solar Panel, Battery, Boost module, Relay Module, Soil Moisture Sensor, DC Motor etc. Arduino Uno that is programmed to collect the input signal according to moisture content of the soil and its output is given to the op-amp that will operate the pump. The benefit of employing this technique is to decrease human interference and it is quite feasible and affordable.